Penerapan Pembelajaran Berbasis Permainan Demi Peningkatan Minat Belajar di UPT SD 060935, Medan Johor - Felix Setiawan Peranginangin; Hairani Siregar (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Education is the cornerstone of the nation's progress. Realizing an advanced nation is certainly an ideal to be achieved by every country in the world. It is common knowledge that the progress of a country is influenced by educational factors. The Teaching Campus Program is part of the Merdeka Learn Kampus Merdeka (MBKM) policy which aims to broaden the competencies students have by providing an opportunity for students to learn outside the classroom by providing assistance to teachers or education staff at the basic education level. The Merdeka Campus is a form of learning in universities that is autonomous and flexible so as to create a learning culture that is innovative, not restrictive, and in accordance with the needs of students. In this activity, the writer as a student of the Social Welfare Study Program, Faculty of Social and Political Sciences, took part in the Teaching Campus Program from Merdeka Learning Campus Teaching (MBKM) at UPT SD 060935, Medan Johor. During its implementation, the authors apply Game-Based Learning to Grade 4 UPT SD 060935 students. The purpose of student participation in the Teaching Campus program is a process of adding relationships, adding experience outside the world of lectures, developing students' insights, character and soft skills.